Pengaruh Insentif terhadap Kinerja Karyawan Dengan Masa Kerja Sebagai Variabel Moderasi Dikantor Pusar Redaksi Harian Pagi Lamongan - Sahari; Musarofah, Siti; Wicaksono, Arian Yusuf (Program Studi Manajemen Fakultas Ekonomika dan Bisnis Universitas Majalengka, 2024)
This study aims to analyze the effect of incentives on employee performance with work tenure as a moderating variable at the Central Office of the Lamongan Morning Daily Editorial Office. Using a quantitative approach with regression analysis, this study involved 50 employees as respondents. The analysis results show that incentives have a positive and significant effect on employee performance (t = 2.406; p < 0.05). However, work tenure does not moderate the relationship between incentives and employee performance (t = 0.050; p > 0.05). This study concludes that incentives are an important factor in improving employee performance, but the role of work tenure is not significant in strengthening this relationship. The practical implication of this study is the need for the company to design effective incentive strategies to enhance employee productivity, regardless of their work tenure.